HIV-related stigma among healthcare providers working within infectious diseases and gynecology and obstetrics at a large teaching hospital in Denmark. Issue 5 (4th May 2023) - Moseholm, E.; Wilken-Jensen, C.; Weis, N.
ABSTRACT: HIV-related stigma experienced in healthcare settings may be particularly detrimental to people with HIV (PWH). This study aims to examine the drivers of stigma and enacted HIV-related stigma among healthcare providers working in HIV and non-HIV care at a large teaching hospital in Denmark. In total, 162 providers working in gynecology and obstetrics, and 57 providers working in infectious diseases completed the "Measuring HIV stigma and discrimination among health facility staff" questionnaire. Compared to providers working in infectious diseases, providers working in gynecology and obstetrics had less training in infection control, HIV, and stigma, and although their level of worry and negative attitudes toward PWH was overall low, they were more like to use extra precaution measures (e.g., double gloves) when caring for PWH (20% versus 0%). Addressing HIV-related stigma in healthcare is important, as any amount of HIV-related stigma from providers has the potential to compromise the patients' engagement in care and health outcomes.